Express 4x/(x^2-9)-2/(x+3) as a single fraction in its simplest form

4x/(x2-9)-2/(x+3) = 4x/((x+3)(x-3))-2/(x+3) = 4x/((x+3)(x-3))-2(x-3)/((x+3)(x-3)) = (4x-2(x-3))/((x+3)(x-3)) = (2x+6)/((x+3)(x-3) = (2(x+3))/((x+3)(x-3)) = 2/(x-3)

Answered by Charles S. Maths tutor

8022 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

What are the solutions of (x^3)+6 = 2(x^2)+5x given x = 3 is a solution?


What is differentiation and how do I do it?


Using first principles find the differential of x^2


Show the sum from n=0 to 200 of x^n given that x is not 1, is (1-x^201)/(1-x) hence find the sum of 1+2(1/2)+3(1/2)^2+...+200(1/2)^199


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences